The Effect of Overconfidence Bias and Representativeness Bias on Investment Decision With Risk Tolerance as Mediating Variable - Yessi Rianita Sihombing; Raeesah Shalsabila Anjani Prameswary (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This research is intended to determine the effect of overconfidence bias and representative bias on investment decisions with risk tolerance as a mediating variable. The object of this research is investors who invest in the Indonesian Capital Market. The technique of collecting data is by using a questionnaire through online media and a literature study with the criteria of active investors with a sample of 200 investors. Data analysis in this study uses an alternative method of Structural Equation Modeling (SEM) version 3.0. The first stage in this research is to test the validity of each variable's questions along with their reliability. The second stage examines the relationship between overconfidence bias and representativeness bias on investment decisions with risk tolerance as a mediating variable. The results of this study indicate that the overconfidence bias variable and the representative bias have a significant positive effect on investment decisions either directly or through the mediating risk tolerance variable.